The Impact of regular physical activity on the general well-being of physically disabled adults in the Kumasi Metropolis - Cudjoe, Mary (2016)
A thesis submitted to the Department of Community Health, College of Health Sciences, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the Msc Degree in Disability, Rehabilitation and Development.